Latin America and the Caribbean SARS-Cov-2 surveillance: Longitudinal trend analysis - Post, Lori; Ohiomoba, Ramael O.; Maras, Ashley; Watts, Sean J.; Moss, Charles B.; Resnick, Danielle (JMIR Publications, 2021)
SARS-CoV-19, the virus that causes COVID-19, is a global pandemic that has placed unprecedented stress on national economies, food systems and healthcare resources in Latin America and the Caribbean (LAC). This region has become an epicenter for the coronavirus, with Brazil and Mexico leading the globe in deaths following the U.S. in death count. Existing surveillance provides a proxy on COVID-19 caseload and deaths; however, these measures make it difficult to identify shifts to the pandemic and changes in the speed and acceleration in COVID-19. Accordingly, we provide an enhanced surveillance system to complement static metrics with dynamic ones that inform hen there are shifts and where explosive growth is likely to occur in LAC.